Balloon dilation of the Eustachian tube with a seeker‐based device: A registry of 169 patients. Issue 5 (10th September 2021) - Standring, Robert T.; O'Malley, Ellen M.; Greene, Joshua B.; Russell, Joseph L.; McCoul, Edward D.
Abstract: Objective: To collect real‐world data on the safety and effectiveness of balloon dilation of the Eustachian tube using a seeker‐based device in patients with persistent/chronic symptoms of Eustachian tube dysfunction. Methods: A multicenter, prospective, single‐arm registry was conducted from June 2018 through August 2020 at 10 US centers, including tertiary care and private practices. Primary endpoints included mean change from baseline in the 7‐item Eustachian Tube Dysfunction Questionnaire (ETDQ‐7) and the serious related adverse event rate. Secondary endpoints include changes in middle ear assessments, surgical intervention rate, and changes in Sino‐Nasal Outcome Test and Work and Activity Impairment (WPAI) questionnaires. Results: A total of 169 participants were treated with balloon dilation of the Eustachian tube, with 166 and 154 participants completing the 6‐week and 6‐month follow‐ups, respectively. Repeated measures analysis of the change in ETDQ‐7 scores indicated statistically significant improvement (−2.1; 95% CI −2.40, −1.84; P  < .0001) at 6‐month follow‐up. The minimum clinically important difference of improvement was achieved by 85% of participants at 6 months. Four nonserious adverse events were reported. Middle ear functional assessments were improved in the majority of participants with abnormal baseline findings. There were no statistically significant differences in the change from baseline ETDQ‐7 scores between participants who had concurrent procedures and those who did not. WPAI scores demonstrated significant improvement. Conclusion: Real‐world evidence supports the clinical studies demonstrating that balloon dilation of the Eustachian tube with a seeker‐based device is a safe and effective procedure to treat ETD symptoms. Level of evidence: 3 Abstract : The purpose of this current study was to gather effectiveness and safety data for BDET using a seeker‐based device in real‐world settings. We conclude that balloon dilation of the Eustachian tube with a seeker‐based device is a safe and effective procedure to treat ETD symptoms.